The Role of TikTok and Instagram in Vocabulary Learning Among Indonesian Gen Z Learners - Gracendy Aluz Clarita Budiono (Universitas Teknologi Yogyakarta, 2025)
Discuss about English as a Foreign Language (EFL) learning imply in Indonesia, many Gen Z learners still struggle to develop strong vocabulary skills despite early instruction and curriculum support. Traditional classroom methods often fail to meet the digital preferences and habits of this generation, who are more engaged with visual, fast-paced, and interactive media. Previous studies have explored digital media in education extensively but have paid little attention to short-form video platforms such as TikTok and Instagram Reels in vocabulary learning, particularly in the Indonesian EFL context. This study addresses this gap by investigating the role of these platforms in supporting vocabulary acquisition. Using quantitative descriptive methods, this study collected data from 33 Gen Z college students through an online questionnaire. The results were analyzed using percentage-based frequency tables and descriptive interpretations. The findings suggest that these platforms contribute significantly to incidental vocabulary learning due to their multimodal features and repetitive and engaging content. This study highlights the importance of aligning language instruction with learners’ digital environments. Future research should explore how educators can integrate these platforms into formal instruction to enhance learning outcomes. A key recommendation for curriculum developers is to recognize social media as a complementary learning resource.